Genomic and epigenetic characterisation of childhood ependymoma - Kilday, John-Paul (2011)
Paediatric ependymomas remain a clinical management challenge, with a relatively poor prognosis when compared to other childhood tumours of the central nervous system. An improved understanding of underlying ependymoma biology may identify new correlates of outcome and potential therapeutic targets. To address this, AffymetrixTM 500K SNP arrays were used to establish the nature and range of genomic imbalances in 63 paediatric ependymomas (42 primary and 21 recurrent). Over 80 % of tumours were analysed against patient-matched constitutional DNA. In addition, the Illumina® GoldenGate® Cancer Panel I array was used to identify differences in methylation profile across 98 paediatric ependymomas (73 primary and 25 recurrent). While collective assessment revealed the most common anomalies, specific aberrations were characteristic of certain ependymoma subgroups, particularly those relating to tumour location, patient age, disease recurrence and patient prognosis. The genomic imbalance of 15 selected candidate genes (NSL1, DNAJC25, NAV1, CDKN2A, CHI3L1, HOXA5, TXN, BNIPL, and PRUNE) were confirmed by quantitative Polymerase Chain Reaction. Genomic gain involving regions of chromosome 1q were associated with an unfavourable patient outcome, such as the focal locus on 1q21.3 encompassing PRUNE. The genomic gain of PRUNE correlated with an increased encoded protein expression, as assessed by immunohistochemistry (IHC).